Configurações das relações de poder no Serviço de Atendimento Móvel de Urgência de Belo Horizonte - Isabela Silva Cancio Velloso (2011)
Emergency care in Brazil constitutes a challenge to be addressed within the proposal for effectuation of integral care. To decentralize emergency care performed only in emergency services, it was established, in 2003, the Emergency Care National Policy. In this Policy, prehospitalcomponent has envisaged deployment of Pre-hospital Emergency Medical Service (SAMU). In Belo Horizonte, SAMU deployment was a milestone of emergency policy because it has qualified the actions of health system, anticipating the hospital care. In that structure, there are particular relations of a work organization, with fights for space and defense of interests, which leads us to reflect on how social actors are part of a system of positions and relations. Some strains have been present in the relations between professionals themselves, as well as in relationships with professionals from other levels of health system.Understanding these tensions involves questions about how practices are organized in that context. The analysis of practices helps to understand how the arrangements are established and how they are admitted and accepted in a given time. This way, poststructuralism offerstheoretical and philosophical resources to develop this study, since it can help to answer questions related to how practices are organized in a given scenario. It has on central position the notion that power is not limited to formally established institutions, but it is inherent in all relationships. SAMU is a privileged setting of power relations, which reflect the uniqueness and the conflicts inherent in the work of a professional team that develops their practices within close relationships with other professionals from other healthcare levels. The aim of this study was to understand how power relations experienced by SAMUprofessionals from Belo Horizonte is configured, considering them as social practices that constitute daily work process. Methodology used was the qualitative case study. The study setting was the SAMU in Belo Horizonte and the subjects were 31 (thirty one) professionals of the Service. Data were collected through semi-structured interviews and submitted to discourse analysis, organized in three analytical categories. At first category, power as social practice in the SAMU, it was proceeded an analysis on the constitution of power in the daily practices of team work. In the second category, Emergency Medical System: work at thewindow, it was discussed the issue of visibility as a factor of organization of power in structure of work. In third category, management of difference: the issue of territories demarcation, it was discussed the issue of professional boundaries and territories definition of performance considering daily struggles in SAMU scenario. In all categories, we attempted to relate power relations with practices experienced by SAMUs team works. Considering ubiquity of power relations, the analysis in the context of SAMU contributed to the understanding of its role in established relationships and to understand strategies employed to contain its effects. This way, its necessary to consider that knowledge is inseparable from practice and is also inseparable from the form, rules, activities and speeches.